Lines in the forest: internal territorialization and local accomodation in West Kalimantan, Indonesia (1865-1979) - Wadley, R.L. (2003)
The history of internal territorialization in West Kalimantan, Indonesia, reveals the interplay between state and local concepts of territory. Both colonial and national authorities sought to divide natural resources and ethnic groups through boundary making, and local peoples have accomodated and challenged state concepts of territory in their competition over natural resources. This histroy highlights a common situation in which local people incorporate state boundary concepts in order to make claims on resources in a way the state recognizes. Yet indigenous concepts of territory and resource claims persist as local people seek multiple, practical ways of securing rights to resources, and as the power of the state flactuates over time.